Free radical scavenging synergism of fucoxanthin with lipophilic plant products. Issue 5 (4th March 2023) - Nurcahyanti, Agustina Dwi Retno; Satriawan, Natasha; Sharopov, Farukh
Abstract: Fucoxanthin demonstrates potential bioactivity, gaining greater interest with many prospective applications. The fundamental activity of fucoxanthin is antioxidant. However, some findings also report the pro-oxidant potential of carotenoids in particular concentrations and environments. In many applications, fucoxanthin requires additional materials to improve bioavailability and stability, such as lipophilic plant products (LPP). Despite much-growing evidence, little is known how fucoxanthin interacts with LPP, which is susceptible to an oxidative reaction. We hypothesised that lower concentration of fucoxanthin exerts a synergistic effect in combination with LPP. The low molecular weight of LPP may exhibit greater activity than long-chain LPP, and so it does with the concentration of unsaturated moieties. We performed free radical-scavenging assay of fucoxanthin combined with some essential oils and edible oils. Chou-Talalay theorem was employed to depict the combination effect. The current study demonstrates a staple finding and constitutes theoretical viewpoints before further fucoxanthin's utilization with LPP. Graphical Abstract: UF0001